Cerebral radiation necrosis complicating stereotactic radiosurgery for arteriovenous malformation. Issue 6 (June 1990) - Statham, P; Macpherson, P; Johnston, R; Forster, D M; Adams, J H; Todd, N V
Abstract : A patient presented with symptoms and signs of raised intracranial pressure and increasing focal deficit 13 months after stereotactic radiosurgical treatment of an arteriovenous malformation (AVM). Computed Tomography (CT) showed a mass lesion at the site of the previous abnormality typical of radiation necrosis, but with features identical to those of a malignant neoplasm. Biopsy confirmed cerebral radiation necrosis. The radiation dose was 25 Gray to the periphery of two overlapping 14 mm collimator fields, delivered in a single dose. Treatment with steroids led to improvement in the symptoms and signs of raised intracranial pressure, but not the focal deficit. Radiation necrosis is a consequence of the large doses required to obliterate AVMs and is a limiting factor in their treatment. It is important for clinicians referring patients for stereotactic radiosurgery to be aware of this complication, and to be able to recognise and treat it.